Forecast and verification of the active compounds and latent targets of Guyuan decoction in treating frequently relapsing nephrotic syndrome based on network pharmacology - Haiyun Wang; Junjie Shi; Binbin Tang; Yanfeng Liu; Qili Wang (Renal Failure)
Background Our study majorly utilizes network pharmacology combined with molecular docking to explore the latent active components and associated pivotal targets of Guyuan Decoction (GYD) in the treatment of frequently relapsing nephrotic syndrome (FRNS).Methods All active components and latent targets of GYD were retrieved from TCMSP database. The target genes for FRNS in our research were obtained from the GeneCards database. The drug-compounds-disease-targets (D-C-D-T) network was established using Cytoscape 3.7.1. STRING database was applied to observe the protein interaction. Pathway enrichment analyses (GO and KEGG) were conducted in R software. Moreover, molecular docking was employed to further validate the binding activity. MPC-5 cells were treated with adriamycin to mimic FRNS in vitro and to determine the effects of luteolin on modeled cells.Results A total of 181 active components and 186 target genes of GYD were identified. Meanwhile, 518 targets related to FRNS were also revealed. Based on the intersection using a Venn diagram, 51 common latent targets were recognized to be associated with active ingredients and FRNS. Additionally, we identified the biological processes and signaling pathways involved in the action of these targets. Molecular docking analyses illustrated that AKT1 and CASP3 interacted with luteolin, wogonin, and kaempferol, respectively. Moreover, luteolin treatment enhanced the viability but inhibited the apoptosis of adriamycin-treated MPC-5 cells via regulating AKT1 and CASP3.Conclusion Our study forecasts the active compounds, latent targets, and molecular mechanisms of GYD in FRNS, which helps us to understand the action mechanism of GYD in FRNS comprehensive treatment.